Can preoperative serum thyroglobulin levels predict the risk of malignancy? Results from prospective analysis of biochemical predictors of malignancy in thyroid nodules - Hulikal, Narendra; Azhagamuthu, RE; Banoth, Manilal; Chowhan, Amith Kumar; Yutla, Mutheswaraiah; Sachan, Alok (Acta otorhino-laryngologica italica, 2020)
Although thyroid nodule is a common presentation, malignancy is rare. The present study investigated biochemical predictors of malignancy in enlarged thyroid. This is a prospective study of all willing patients 18 to 70 years presenting with a complaint of thyroid swelling and who underwent definitive surgery over a period of 19 months. All subjects were initially evaluated with detailed history, physical examination, ultrasonography of neck and fine needle aspiration cytology (FNAC). Preoperative estimation of serum thyroid stimulating hormone (TSH), thyroglobulin (Tg) and anti-thyroglobulin (anti Tg) antibody was obtained. The treatment plan was based on FNAC results and included hemi- or total thyroidectomy. During the study period, 110 patients underwent thyroidectomy, and met the selection criteria, of which 47 patients had malignancy on final histopathology. The majority were females, 30 to 60 years old. Median serum Tg, TSH and anti Tg levels in the benign group were, respectively 29 ng/ml, 1,6 mIU/L and 1,1 IU/ml, whereas in malignant nodules they were 162 ng/ml. 1,7 mIU/L and 0,9 IU/ml. On receiver operating characteristic curve analysis, a Tg cut off value of 53 ng/ml predicted malignancy risk with a sensitivity and specificity of 72% and 73%, respectively (p < 0.001). Our study showed the utility of preoperative Tg in predicting risk of malignancy. Its role should be further explored especially in the backdrop of indeterminate cytology through a larger study.